Who Killed Stjepan Radić? Interpretations and the Culture of Memory - Smiljanić, Vlatko; Šagi, Bruno (Historical Thought, 2025)
This paper researches the 1928 assassination in the National Assembly of the Kingdom of Serbs, Croats and Slovenes and the death of Stjepan Radić through an analysis of historiographical interpretations, political context, and cultural reception of the event. The aim is to identify the differences in interpretations of the assassination and the circumstances of Radić’s death, and to examine how these events shaped Croatian political culture. By applying the method of comparative analysis of sources, memoir materials, and scholarly literature, the study explores the dynamics of political violence, the ideologisation of memory, and the symbolic potential of Radić’s death. The article contributes to a deeper understanding of the political controversies in interwar Yugoslavia and the long-term effects of the assassination on Croatian-Serbian relations and national memory.